Restrained Flexure of Brittle-Matrix Composite Structures - M. Janas; J. Sokół-Supel (Engineering Transactions, 2015)
Restrained flexure analysis concerns transversal bending of flat structures with in-plane displacements at supports prohibited or restricted. If the material characteristics are different in tension and in compression, these restraints generate important membrane forces (the arching action effect). It strengthens considerably the structure, but renders its response strongly nonlinear and unstable. In a recent introductory study the authors concluded that their old approximate analytical approach to restrained flexure of elastic-plastic beams and slabs gives qualitatively good results and may be useful to replace cumbersome numerical procedures. Here, a parametric study using an incremental FEM analysis is performed enabling the determination of input data needed for an elementary but reliable approximate approach. Different load and support configurations for beam systems are considered and the structure sensitivity to support compliance is studied. Numerical and approximate analytical results are compared with results of a series of collapse tests on elastically restrained RC beams.